Multiple Literacies Theory: how it functions, what it produces - Diana Masny (Perspectiva)
At the moment, there are two literacy theories that seem to dominate the research on literacies. They are known as the New Literacy Studies (NLS) (BARTON; HAMILTON; IVANI?; 2002; STREET, 2003) and Multiliteracies (COPE; KALANTZIS, 2009). This article is about a different theory, Multiple Literacies Theory (MLT) that demarcates itself from them ontologically and epistemologically. It will also highlight aspects of NLS and Multiliteracies in order to point out the differences with MLT. This article aims to put forward the major concepts that underlie this theory and present vignettes from a study examining how perceptions of writing systems in multilingual children contribute to reading, reading the world and self as texts.